The national digital library as a knowledge portal towards realisation of knowledge-based society: a statistical analysis of usage / Azman Ibrahim - Ibrahim, Azman (2002)
To improve the design of the National Digital Library Web site and facilitate user access to it, a Web usage analysis was conducted through examination of statistics generated by Web tracking software, which many library managers are now implementing. The study examines the geographic distribution of users, usage patterns of the web site and the computer environment information. In addition the study also measure the effectiveness of Mylib's marketing efforts. The findings of the study concentrate on identifying web page design problems, thus allowing the establishment of recommendations that will modify standards of the web page design and improve strategies of Mylib promotion. The study also explores internet-readiness of Malaysian society in their efforts to leapfrog into a knowledge-based society.